Alleviation of Nitrogen and Sulfur Deficiency and Enhancement of Photosynthesis in Arabidopsis thaliana by Overexpression of Uroporphyrinogen III Methyltransferase (UPM1) - Garai, Sampurna; Tripathy, Baishnab C. (Frontiers in Plant Science, 2018)
Siroheme, an iron-containing tetrapyrrole, is the prosthetic group of nitrite reductase (NiR) and sulfite reductase (SiR); it is synthesized from uroporphyrinogen III, an intermediate of chlorophyll biosynthesis, and is required for nitrogen (N) and sulfur (S) assimilation. Further, uroporphyrinogen III methyltransferase (UPM1), responsible for two methylation reactions to form dihydrosirohydrochlorin, diverts uroporphyrinogen III from the chlorophyll biosynthesis pathway towards siroheme synthesis. AtUPM1 [At5g40850] was used to produce both sense and antisense plants of Arabidopsis thaliana in order to modulate siroheme biosynthesis. In our experiments, overexpression of AtUPM1 signaled higher NiR (NII) and SiR gene and gene product expression. Increased NII expression was found to regulate and enhance the transcript and protein abundance of nitrate reductase (NR). We suggest that elevated NiR, NR and SiR expression must have contributed to the increased synthesis of S containing amino acids in AtUPM1overexpressors, observed in our studies. We note that due to higher N and S assimilation in these plants, total protein content had increased in these plants. Consequently, chlorophyll biosynthesis increased in these sense plants. Higher chlorophyll and protein content of plants upregulated photosynthetic electron transport and carbon assimilation in the sense plants. Further, we have observed increased plant biomass in these plants, and this must have been due to increased N, S and C assimilation. On the other hand, in the antisense plants, the transcript abundance, and protein content of NiR, and SiR was shown to decrease, resulting in reduced total protein and chlorophyll content. This led to a decrease in photosynthetic electron transport rate, carbon assimilation and plant biomass in these antisense plants. Under nitrogen or sulfur starvation conditions, the overexpressors had higher protein content and photosynthetic electron transport rate than the wild type (WT). Conversely, the antisense plants had lower protein content and photosynthetic efficiency in N-deficient environment. Our results clearly demonstrate that upregulation of siroheme biosynthesis leads to increased nitrogen and sulfur assimilation, and this imparts tolerance to nitrogen and sulfur deficiency in Arabidopsis thaliana plants.